In situ and in vitro nutritional evaluation of rumen-protected lipids - F. Rossi; F. Masoero; A.M. Pulimeno (Italian Journal of Animal Science, 2010)
Rumen-protected lipids are a class of products which is increasingly used in ruminant nutrition even if the results are not homogeneous. The different results may be due to different analytical or technological characteristics. Aim of this work was therefore to compare the in situ rumen behaviour of different soaps as well as their in vitro intestinal digestibility.